2021
DOI: 10.3389/fcell.2021.673813
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Roles of Autophagy and Autophagy Proteins in Host Cells During Toxoplasma gondii Infection and Potential Therapeutic Implications

Abstract: Toxoplasma gondii is an obligate intracellular protozoan that can cause encephalitis and retinitis in humans. The success of T. gondii as a pathogen depends in part on its ability to form an intracellular niche (parasitophorous vacuole) that allows protection from lysosomal degradation and parasite replication. The parasitophorous vacuole can be targeted by autophagy or by autophagosome-independent processes triggered by autophagy proteins. However, T. gondii has developed many strategies to preserve the integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…Toxoplasma gondii , the causative agent of toxoplasmosis, is known to cause encephalitis, retinitis and miscarriage [ 181 ] Data reported an increase of mitochondria fragmentation of human fibroblasts cells infected with the T. gondii and these mitochondria were recruited to the parasitophorous vacuole [ 158 , 182 ]. In addition, infected cells had metabolic perturbations of mitochondrial glycolysis [ 160 ] and OXPHOS complex [ 161 ], as well as increase of mitochondrial ROS, changes the amount of OXPHOS components and many other mitochondrial-related proteins [ 158 , 183 ].…”
Section: Mitochondrial Bioenergetics and Dynamics In Infectious Diseasesmentioning
confidence: 99%
“…Toxoplasma gondii , the causative agent of toxoplasmosis, is known to cause encephalitis, retinitis and miscarriage [ 181 ] Data reported an increase of mitochondria fragmentation of human fibroblasts cells infected with the T. gondii and these mitochondria were recruited to the parasitophorous vacuole [ 158 , 182 ]. In addition, infected cells had metabolic perturbations of mitochondrial glycolysis [ 160 ] and OXPHOS complex [ 161 ], as well as increase of mitochondrial ROS, changes the amount of OXPHOS components and many other mitochondrial-related proteins [ 158 , 183 ].…”
Section: Mitochondrial Bioenergetics and Dynamics In Infectious Diseasesmentioning
confidence: 99%
“…argued that this process occurs under the regulation of IFN-stimulated genes ( Bhushan et al., 2020 ). Nevertheless, in human endothelial cells infected by type II strains, ubiquitinated K63 is recruited by IFN-γ to induce the fusion of lysosomes and PVM to T. gondii ( Clough et al., 2016 ; Subauste, 2021 ). NDP52 and p62 are subsequently recruited around PV in the absence of LC3 and ATG16L ( Figure 2C ).…”
Section: The Interplay Of T Gondii and Host Cell A...mentioning
confidence: 99%
“…Studies on T. gondii have shown that autophagosomes cannot directly kill T. gondii in parasitophorous vacuoles, but autophagy and autophagy-related proteins can promote the killing effect of the non-canonical IFN-γ-dependent autophagy pathway against T. gondii ( Sasai et al, 2018 ; Zhu et al, 2019 ; Subauste, 2021 ). Next, we tried to research the effect of C3 on killing T. gondii by IFN-γ-activated macrophages.…”
Section: Resultsmentioning
confidence: 99%
“…It mainly affects the central nervous system (CNS) ( Schluter and Barragan, 2019 ). T. gondii are targeted by a non-canonical autophagy pathway in IFN-γ-activated cells to restrict parasite growth ( Selleck et al, 2015 ; Subauste, 2021 ). T. gondii is an important model for studying infection and immunity and is a relatively mature in vivo and in vitro infection model.…”
Section: Introductionmentioning
confidence: 99%